Weak spots inhibition in the Mycobacterium tuberculosis antigen 85C target for antitubercular drug design through selective irreversible covalent inhibitor-SER124. Issue 7 (3rd May 2022) - Adewumi, Adeniyi T.; Elrashedy, Ahmed; Soremekun, Opeyemi S.; Ajadi, Mary B.; Soliman, Mahmoud E. S.
Abstract: Mycobacterium tuberculosis ( Mtb ) encoded secreted antigen 85 enzymes (Ag85A/Ag85B/Ag85C) play that critical roles in the virulence, survival and drug-resistant TB of the pathogen. Ag85 proteins are potential antitubercular drug targets because they are essential in the catalytic synthesis of trehalose moieties and mycolic acid attachment to the Mtb cell wall. Recently, experimental protocols led to the discovery of a selective covalent Ag85 inhibitor, β-isomer monocyclic enolphosphorus Cycliphostin (CyC8β ) compound, which targets the Ag85 serine 124 to exhibit a promising therapeutic activity. For the first time, our study unravelled the structural features among Mtb Ag85C homologs and motions and dynamics of Ag85C when the CyC8β bound covalently and in open model conformations to the protein using bioinformatics tools and integrated Molecular dynamics simulations. Comparative Ag85C sequence analysis revealed conserved regions; 70% active site, 90% Adeniyi loop L1 and 50% loop L2, which acts as a switch between open and closed conformations. The average C-α atoms RMSD (2.05 Å) and RMSF (0.9 Å) revealed instability and high induced flexibility in the CyC8β covalent-bound compared to the apo and open model systems, which displayed more stability and lower fluctuations. DSSP showed structural transitions of α-helices to bend and loops to 310 -helices in the bound systems. SASA of CyC8β covalent bound showed active site hydrophobic residues exposure to huge solvent. Therefore, these findings present the potential opportunity hotspots in Ag85C protein that would aid the structure-based design of novel chemical entities capable of resulting in potent antitubercular drugs. Communicated by Ramaswamy H. Sarma